MORPHOMETRIC STUDY OF PTERION AND ITS CLINICAL SIGNIFICANCE - Nayak, Gyanaranjan; Bhusan Mohanty, Biswa; Ranjan Das, Saurjya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Pterion is an area formed by the union of frontal, parietal, temporal, and sphenoid bones. It exhibits variations in the sutural pattern of fusion of constituent bones. Basing on this, the pterion can be classified into four varieties. According to Murphy, these are sphenoparietal, frontotemporal, stellate, and epipteric. The anatomical location of the pterion is necessary for the surgical management of extradural hemorrhage, aneurysm, and brain tumors located in the anterior and middle cranial fossae.The purpose of this study is to find out the prevalence of different varieties of pterion and determine the position of pterion using anatomical landmarks. Methods: The present study included fifty skulls of unknown age and sex. The skulls were studied macroscopically for the anatomical variations of pterion. The distance between the center of the pterion to the midpoint of zygomatic arch and pterion to the frontozygomatic suture was measured using Vernier calipers. Results: The sphenoparietal variety was the most common variety of pterion found in the study followed by the epipteric variety and the stellate variety, respectively. The distance between pterion and back of the frontozygomatic suture was found to be 3.48 Â± 0.21 cm on the right side and 3.41 Â± 0.16 cm on the left side. The distance between pterion and the midpoint of upper border of the zygomatic arch was found to be 4.01 Â± 0.19 cm on the right side and 3.94 Â± 0.2 cm on the left side. Conclusion: The findings will be helpful for radiologists and neurosurgeons.